Reflective and Automatic Processes in Health Care Professional Behaviour: a Dual Process Model Tested Across Multiple Behaviours. Issue 3 (20th March 2014) - Presseau, Justin; Johnston, Marie; Heponiemi, Tarja; Elovainio, Marko; Francis, Jill J.; Eccles, Martin P.; Steen, Nick; Hrisos, Susan; Stamp, Elaine; Grimshaw, Jeremy M.; Hawthorne, Gillian; Sniehotta, Falko F.
Abstract: Background: Clinicians' behaviours require deliberate decision-making in complex contexts and may involve both impulsive (automatic) and reflective (motivational and volitional) processes. Purpose: The purpose of this study was to test a dual process model applied to clinician behaviours in their management of type 2 diabetes. Methods: The design used six nested prospective correlational studies. Questionnaires were sent to general practitioners and nurses in 99 UK primary care practices, measuring reflective (intention, action planning and coping planning) and impulsive (automaticity) predictors for six guideline-recommended behaviours: blood pressure prescribing ( N  = 335), prescribing for glycemic control ( N  = 288), providing diabetes-related education ( N  = 346), providing weight advice ( N  = 417), providing self-management advice ( N  = 332) and examining the feet ( N  = 218). Results: Respondent retention was high. A dual process model was supported for prescribing behaviours, weight advice, and examining the feet. A sequential reflective process was supported for blood pressure prescribing, self-management and weight advice, and diabetes-related education. Conclusions: Reflective and impulsive processes predict behaviour. Quality improvement interventions should consider both reflective and impulsive approaches to behaviour change.